2012
DOI: 10.5507/fot.2012.004
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms (Bacillariophyceae) from the Bolivian Altiplano: three new araphid species from the Desaguadero River draining Lake Titicaca.

Abstract: Abstract:Three new araphid diatom species, Pseudostaurosira decipiens e. Morales, G. Chávez et eCtor, P. sajamaensis e. Morales et eCtor and Staurosira kjotsunarum e. Morales, Novais et eCtor are described from a single sample taken from the Desaguadero River in the Bolivian Altiplano. These species clearly belong in their respective genera as evidenced by their morphological features studied using light (LM) and scanning electron microscopy (SEM). Pseudostaurosira decipiens is unique in its genus because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…Manguin (1964) expressed a similar view of predominant cosmopolitism based on samples from the Andes near Lima, Peru (ranked higher than Bolivia as a biodiverse country), reporting the presence of 52.5% of cosmopolitan taxa out of a total of 392 from 10 samples; although at least two of these samples were from below 2000 m above sea level (asl), indicating that they were not truly Altiplanic localities. Morales et al (2012) challenged this current view on Andean diatoms since their study of a single epipsammon sample from the Bolivian Desaguadero River yielded 228 taxa, more than a quarter of those reported by Rumrich et al (2000) based on 350 samples and covering a geographical range from Argentina to Venezuela. Based on a taxonomic comparison with local regional and worldwide literature, Morales et al (2012) determined that more than 80% of the taxa from Desaguadero River were not cosmopolitan, a fact most probably explained by the little human-related disturbance on the river collection site relative to the higher anthropic effects on the sites sampled by Rumrich et al (2000).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Manguin (1964) expressed a similar view of predominant cosmopolitism based on samples from the Andes near Lima, Peru (ranked higher than Bolivia as a biodiverse country), reporting the presence of 52.5% of cosmopolitan taxa out of a total of 392 from 10 samples; although at least two of these samples were from below 2000 m above sea level (asl), indicating that they were not truly Altiplanic localities. Morales et al (2012) challenged this current view on Andean diatoms since their study of a single epipsammon sample from the Bolivian Desaguadero River yielded 228 taxa, more than a quarter of those reported by Rumrich et al (2000) based on 350 samples and covering a geographical range from Argentina to Venezuela. Based on a taxonomic comparison with local regional and worldwide literature, Morales et al (2012) determined that more than 80% of the taxa from Desaguadero River were not cosmopolitan, a fact most probably explained by the little human-related disturbance on the river collection site relative to the higher anthropic effects on the sites sampled by Rumrich et al (2000).…”
Section: Introductionmentioning
confidence: 90%
“…Bao et al, 1999;Sylvestre et al, 2001;Servant & Servant-Vildary, 2003;Vélez et al, 2005;Ekdahl et al, 2008, among many others). The recent major taxonomical study of Andean diatoms produced by Rumrich et al (2000) also reported a low number of new species and a surprising high number of common elements (42% of 888 recorded taxa) with the European diatom flora (see discussion in Morales et al, 2012). These data are paradoxical for a country counted among those with the highest biological diversity in the world (Ibisch & Mérida, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El cordón montañoso andino, con sus grandes extensiones, variada topografía y diferentes condiciones climáticas crea un escenario ideal para el desarrollo de una flora diatomológica heterogénea (Rumrich et al, 2000). Es por ello que en las últimas décadas se ha incrementado el interés por conocer la diatomoflora de humedales de altura y entre los aportes sobre diatomeas de los Andes se pueden citar las contribuciones realizadas por Rumrich et al (2000); Álvarez- Blanco et al (2011); Blanco et al (2013); Díaz & Maidana (2005); González Achem et al 2014; Maidana & Seeligmann (2006; Maidana et al (2009Maidana et al ( y 2011; Morales et al (2012); Seeligmann & Maidana (2003, 2013; Seeligmann et al (2008), entre otros. Estos estudios, en su mayoría, se centraron en la taxonomía, quedando como incógnita la información relacionada con los factores que regulan la riqueza y abundancia de las comunidades planctónicas y bentónicas.…”
Section: Palabras Claveunclassified
“…Para algunos autores las Fragilariaceae son frecuentes en alta montaña, donde estos organismos deben adaptarse a bajas temperaturas, con prolongados períodos con hielo, cambios bruscos de las condiciones físicoquímicas, bajas concentraciones de nutrientes y alta UV (Schmidt et al, 2004a). Contribuciones realizadas para ambientes de alta montaña por otros autores (Álvarez-Blanco et al, 2011;Morales & Edlund, 2003;Morales et al, 2010Morales et al, , 2012Rumrich et al, 2000;Schmidt et al, 2004a;2004b, entre otros) indican que Staurosira es el género encontrado con mayor frecuencia en estos ambientes, seguido de Pseudostaurosira, siendo Staurosirella el menos frecuente. Sin embargo, debe considerarse que los autores mencionados tienen conceptos taxonómicos diferentes para la circunscripción de estos géneros.…”
Section: Conclusionesunclassified